Editorial, Volume 5, Issue 2 - Kristy L Archuleta (Journal of Financial Therapy, 2015)
This issue’s editorial is inspired by the importance of practitioners’ involvement in the peer review process for a scholarly publication like the Journal of Financial Therapy.
Keywords: editorial; practitioner reviewer; financial therapy